META ANALISIS : ANALISIS KESULITAN MATEMATIS MAHASISWA PADA PERSAMAAN DIFERENSIAL - Novita Sari, Dwi; Erika Dewi, Siska; Khadijah, Siti; Fahira Berutu, Alya; Nabillah, Sarah (JURNAL MathEdu (Mathematic Education Journal), 2024)
The research conducted uses the Meta analysis method by reviewing several articles in journals, articles in research journals are deliberately selected based on their relevance to the research topic and can be accessed online through Google Scholar. This study aims to determine the difficulties of mathematics students in differential equations difficulties faced by students, this problem has previously been researched based on previous studies. Meta analysis is a study in the form of research on similar problems. Previous researchers researched using. Data collection techniques are interviews documentation and tests. The unit of analysis in this study is in the form of data information, namely written documents about student mathematical difficulties in differential equations, In this research analysis used qualitative descriptive qualitative analysis data analysis. The results showed that with the research on students' mathematical difficulties in differential equations can find out what factors cause the problem. By knowing what factors can cause learning difficulties so that the problem can be handled so that it can produce good learning outcomes.